2022
DOI: 10.1186/s13045-022-01367-4
|View full text |Cite
|
Sign up to set email alerts
|

PARP1-MGMT complex underpins pathway crosstalk in O6-methylguanine repair

Abstract: DNA lesions induced by alkylating agents are repaired by two canonical mechanisms, base excision repair dependent on poly(ADP) ribose polymerase 1 (PARP1) and the other mediated by O6-methylguanine (O6meG)-DNA methyltransferase (MGMT) in a single-step catalysis of alkyl-group removal. O6meG is the most cytotoxic and mutagenic lesion among the methyl adducts induced by alkylating agents. Although it can accomplish the dealkylation reaction all by itself as a single protein without associating with other repair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…It is likely that the tumor microenvironment and genomic background contribute to the absence of TLZ activity in mice. We recently reported that PARylated MGMT has increased activity in repairing O 6 -methylguanine lesions, which is dependent on alkylating DNA damage [53]. Since resistance to TMZ can be mitigated with PARP1 inhibitors regardless of MGMT expression, mismatch repair proteins may contribute to O 6 -methylguanine repair when MGMT activity is compromised (including through PARP1 inhibition by drugs like TLZ) [77].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the tumor microenvironment and genomic background contribute to the absence of TLZ activity in mice. We recently reported that PARylated MGMT has increased activity in repairing O 6 -methylguanine lesions, which is dependent on alkylating DNA damage [53]. Since resistance to TMZ can be mitigated with PARP1 inhibitors regardless of MGMT expression, mismatch repair proteins may contribute to O 6 -methylguanine repair when MGMT activity is compromised (including through PARP1 inhibition by drugs like TLZ) [77].…”
Section: Discussionmentioning
confidence: 99%
“…Causing tumor cell death by inducing DNA damage is the main mechanism by which some chemotherapeutic drugs work, while tumor cells rescue themselves from the damage by their own DNA repair function thus creating resistance to chemotherapeutic drugs. O (6)-methylguanine-DNA methyltransferase (MGMT) is an important transferase in the DNA repair process for the elimination of toxic and premutagenic DNA adduct O 6 -methylguanine from cells [ 100 ]. Lipoic acid, disulfide-containing substance, is a naturally occurring cofactor for the mitochondrial enzymes pyruvate dehydrogenase and alpha-ketoglutarate dehydrogenase [ 101 ].…”
Section: Natural Compounds That Reduce Tumor Drug Resistance and Thei...mentioning
confidence: 99%
“…AGT has also recently been shown to directly interact with poly(ADP-ribose) polymerase 1 (PARP1) [ 121 ]. PARP1 functions in BER as well as other DNA repair pathways by adding poly-ADP-ribose chains (PAR) to its protein targets, as well as itself.…”
Section: Functional Implications Of Protein Interactionsmentioning
confidence: 99%
“… Posttranslational modifications of AGT. ( A ) Interactions between AGT and PARP1 were demonstrated by co-immunoprecipitation and western blot (WB) analysis after treating cells with temozolomide (TMZ) [ 121 ] ( top ). Immunoglobulin 1 (IgG1) served as a negative control.…”
Section: Functional Implications Of Protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation